a^(x+y)
When we see an expression like a^(x+y), it means we have a base (a) raised to the power of a sum (x+y)
When we see an expression like a^(x+y), it means we have a base (a) raised to the power of a sum (x+y). To simplify this expression, we can utilize the properties of exponents.
The property we will use here is the power of a sum. According to this property, when we have a base raised to the power of a sum, we can separate it into separate terms raised to that power. Mathematically, it is expressed as:
a^(x+y) = a^x * a^y
So, we can rewrite the expression a^(x+y) as a^x * a^y.
For example, if we have a = 2, x = 3, and y = 4, we can calculate the value of a^(x+y):
a^(x+y) = 2^(3+4)
Using the property of exponents, we can rewrite this as:
2^3 * 2^4
Simplifying further, we get:
8 * 16 = 128
So, in this example, the value of a^(x+y) when a = 2, x = 3, and y = 4 is 128.
More Answers:
Understanding Inverse Functions: A Step-by-Step Guide and ExampleUnderstanding Inverse Symmetry: Definition, Examples, and Mathematical Applications
How to Find the Derivative of the Inverse Function: An Illustrative Example with Step-by-Step Guide